IMPLEMENTASI TEKNOLOGI MELALUI DIGITAL MARKETING DAN INOVASI PRODUK DALAM MENINGKATKAN KESEJAHTERAAN EKONOMI USAHA KECIL MENENGAH PENGOLAHAN TERASI - Zikriatul Ulya; Zulfa Eliza; Mastura (Jurnal Masyarakat Indonesia (Jumas), 2024)
In encouraging the economic prosperity of society, entrepreneurship plays an important role in opening up great opportunities for inclusive economic growth. The role played by terasi Small and Medium Enterprises (UKM) entrepreneurs in the economic ecosystem has become the backbone for the progress and improvement of the economic prosperity of terasi SMEs. SMEs must increase sales by implementing technology and using digital marketing and product innovation to improve welfare. The aim of this research is to analyze the influence of technology implementation through digital marketing and innovation in shrimp paste processing products in improving economic welfare. This type of research is quantitative descriptive. The technique used was purposive random sampling with a sample size of 50 SME respondents. data collection using questionnaires or questionnaires by testing multiple linear regression analysis using IBM Statistics 22. The results of the research show that the results of the partial test (T Test), namely the implementation of technology, has an influence and significance on the economic welfare of terasi SMEs in Langsa City, digital marketing has no effect and no significant to the economic welfare of shrimp paste SMEs in Langsa City, product innovation is influential and significant to the economic welfare of shrimp paste SMEs in Langsa City. The results of the simultaneous test (F test) show that the implementation of technology, digital marketing and product innovation has a significant and influential effect on the economic welfare of terasi SMEs in Langsa City.